Peningkatan Hasil Belajar Matematika Keliling Bangun Datar Melalui Model Team Games Tournament (TGT) Pada Siswa Kelas V UPT SPF SD Inpres Hartaco Indah - Andi Agus Nandi Putra; A. Mutiatul Awaliah; Hamdana Hadaming; Darmansyah Darmansyah (Departement of Mathematics Education, 2024)
This research is a classroom action research that aims to improve the mathematics learning outcomes of the material around the flat shapes of fourth grade students at UPT SPF SD Inpres Hartaco Indah through the Team Games Tournament (TGT) model and was carried out in 2 cycles. In the first cycle, the implementation method uses only the classical lecture method. The classical method alone is ineffective because it makes students bored, thus triggering a lack of enthusiasm in learning so that it has an impact on their learning outcomes, namely not meeting the assessment standards or KKM (Minimum Completeness Criteria). The KKM in class IV mathematics at UPTSPF SD Inpres Hartaco Indah was 80. In cycle II the Team Games Tournament (TGT) model was implemented. The application of this model is able to improve student learning outcomes. This can be proven from the value of learning outcomes of students in the second cycle of mathematics. In cycle I, the classical completeness score was only 46% in the moderate category and then increased in cycle II, namely 83% in the very good category. Based on the results obtained, the use of the Team Games Tournament (TGT) model can be said to have succeeded in increasing the results of learning mathematics on the material around a flat figure.